One-Pot Deprotonative Synthesis of Biarylazacyclooctynones - Hioki, Yuto; Itoh, Mayu; Mori, Atsunori; Okano, Kentaro (Synlett, 2020)
Deprotonative formation of biarylazacyclooctynone (BARAC) from the corresponding enol triflate is described. The reaction furnished the azacyclooctynone within one hour at –78 °C. This process could be performed in one pot from the starting ketone to provide a range of BARAC derivatives in moderate to excellent yields. The protocol enabled the gram-scale formation of the BARAC skeleton by reducing the number of reaction steps. Furthermore, the established method was applied to the synthesis of the BARAC derivative bearing a coumarin moiety.
Keywords: alkynes; bioorganic chemistry; enolate; one-pot reaction; strained molecules